Analisis Pengaruh Lingkungan Kerja, Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Kantor Kelurahan Kabola Kecamatan Kabola Kabupaten Alor - Kace Maucang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Performance is the result or level of success of a person as a whole during a certain period in carrying out tasks compared to work standards, targets or goals or criteria that have been determined in advance and have been mutually agreed upon. However, in carrying out their duties, employees of the Alor Regency Regional Disaster Management Agency still need to pay attention to optimal performance so that it has an impact on achieving the goals of the Alor Regency Kabola willage office Kabola sub-district. For this reason, it is necessary to pay attention to work environment factors, organization culture and organization commitmen. This study aims to determine the effect of work environment, organization culture and organizational commitment on the performance of employees of the Kabola Village office, Kabola district Alor Regency Regional Disaster Management Agency, either partially or simultaneously. Respondents of this study were 15 employees. Data collection using questionnaires, observation, interview and literature review. The data is then analyzed using the t-test to determine the partial effect and the F-test to determine the simultaneous effect on performance with the results of the study being: 1) The variables of work denvironment, organizational culture and organization commitment employee performance have a Pearson product moment correlation value which is above the limit of 0.3 for the validity test. 2) The variables of work denvironment, organizational culture and organization commitment employee performance have a chronbah alpha value which is above the limit of 0.6 for the reliability test. 3) The variables of work denvironment, organizational culture and organization commitment employee performance have a test value for each classic assumption test that is above alpha and passes the classic assumption test. 4) There is an influence of the work environment on Employee Performance at the Kabola sub-district office Alor district, as evidenced by the significance value of the t test which is 0.000 which is smaller than the research alpha value of 5% (0.05); 5) There is an influence of Organizational Culture on Employee Performance at the Kabola sub-district office Alor district, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the research alpha value, which is 5% (0.05); 6) There is an influence of Organizational Commitment on Employee Performance at the Kabola sub-district office Alor district, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the alpha value of the study, which is 5% (0.05); 7) There is an influence of work denvironment, organizational culture and organization commitment on Employee Performance at the Kabola sub-district office Alor district, as evidenced by the significance value of the F test which is 0.000 which is smaller than the research alpha value of 5% (0.05) From the results of the research and research conclusions, the research team suggested to Respondents (employees of the Kabola sub-district office Alor district) that employees are expected to be able to maintain the performance of employees. who have been well organized to date, while continuing to improve themselves considering various changes in current work situation